2012
DOI: 10.1159/000345045
|View full text |Cite
|
Sign up to set email alerts
|

Association between Inflammatory and Obesity Markers in a Swiss Population-Based Sample (CoLaus Study)

Abstract: Objective: To assess the associations between obesity markers (BMI, waist circumference and %body fat) and inflammatory markers (interleukin-1β (IL-1β); interleukin-6 (IL-6); tumor necrosis factor-α (TNF-α) and high-sensitivity C-reactive protein (hs-CRP)). Methods: Population sample of 2,884 men and 3,201 women aged 35–75 years. Associations were assessed using ridge regression adjusting for age, leisure-time physical activity, and smoking. Results: No differences were found in IL-1β levels between participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 59 publications
2
51
1
2
Order By: Relevance
“…It is of note, that, as previously reported in the general population434445, when singly considered, only some cytokines, were variably associated with only some cardiovascular risk factors, thus suggesting that the two scores we utilized do sign comprehensively a biological pathway providing information which is not entirely derivable from any single cytokine. These associations were obtained in healthy individuals taking no medications, thus making sure that our results are not biased by either concomitant overt diseases and/or organ damages, or by ongoing treatments.…”
Section: Discussionmentioning
confidence: 79%
“…It is of note, that, as previously reported in the general population434445, when singly considered, only some cytokines, were variably associated with only some cardiovascular risk factors, thus suggesting that the two scores we utilized do sign comprehensively a biological pathway providing information which is not entirely derivable from any single cytokine. These associations were obtained in healthy individuals taking no medications, thus making sure that our results are not biased by either concomitant overt diseases and/or organ damages, or by ongoing treatments.…”
Section: Discussionmentioning
confidence: 79%
“…A positive correlation between TNF-alpha and BMI has also been reported [137]. Recently, it was reported that elevated plasma levels of TNF-alpha are associated with left ventricular diastolic dysfunction, which is one of the earliest manifestations of left ventricular dysfunction due to diabetes mellitus [138], while administration of TNF-alpha inhibitors leads to an increase of HDL levels [39].…”
Section: Tumor Necrosis Factor-alpha (Tnf-alpha)mentioning
confidence: 96%
“…For example, a recent review and meta-analysis identified 51 cross-sectional studies investigating the positive correlation (r=.36) between obesity in adults and C-reactive protein (a key marker for inflammation) [69]. Similarly, systemic increases in a wide range of inflammatory cytokines such as tumor necrosis factor- alpha (TNF-α), interleukin-6 (IL-6), and adiponectin have also been associated with increasing adiposity [70, 71], and with increased risk for metabolic disorders such as cardiovascular diseases, fatty liver disease, and type 2 diabetes [72, 73]. Despite these various association studies, the causal pathways between obesity, inflammation, and metabolic disease remain incompletely understood.…”
Section: Candidate Mechanisms Underlying Gut Microbiota Induced Obesitymentioning
confidence: 99%